Effectiveness of the National Program for Community Empowerment (PNPM) for Infrastructure Development Accelerated and Geoplanology in District of Marpoyan Damai, Pekanbaru - Riry Fatriadi; Febby Asteriani; Catur Cahyaningsih (UIR PRESS, 2017)
Since 2007 PNPM Urban realize that poverty is a structural problem and multi-dimensional. In PNPM Urban perspective , the complexity of the various dimensions of poverty -related social , political , economic , and asset . this research aim is to know the Effectiveness of the National Program for Community Empowerment for Infrastructure Development Accelerated. In this research , the authors use an explanatory survey research methods . Selected number of samples in the analysis of the effectiveness of PNPM Urban infrastructure improvements are stakeholders involved in PNPM Urban population in the research area of all stakeholders involved in PNPM Urban in District Marpoyan Damai , the authors take purposively respondents who meet the criteria and are associated with research. The results showed that increasing road infrastructure with the PNPM Mandiri. The average improvement of road infrastructure after the PNPM Urban amounted to 35.8 %. The average increase in the quality of infrastructure before the PNPM Urban program is only at 4.4 % per year . This indication shows that roads infrastructure and the quality of the road surface to be increased significantly in the presence of the PNPM Urban Marpoyan Damai in the District . From interviews with relevant stakeholders PNPM Urban, respondents said PNPM Urban was very effective against the improvement of infrastructure in District Marpoyan Damai . Respondents argue that any proposed activity in infrastructure always realized by PNPM Urban . Geological condition of study consists of alluvium Sand, Gravel, Clay, Peat Swamp, Plant Remain in Quaternary age. There are two anticline in this area that is part Western and Southern and fault inferred direction Northwest-Southeast in the middle area of research so that the topography of the area of research a bit wavy and faulted that need observation on land-use planning such as drainage, airport, residential and availability of clean water..